Experimental investigation of in-line and staggered blockages in parallel flowfield channels of PEM fuel cells. (4th May 2016) - Heidary, Hadi; Kermani, Mohammad J.; Advani, Suresh G.; Prasad, Ajay K.
Abstract: The presence of a blockage in the flowfield channel of a PEM fuel cell can potentially enhance mass transfer of reactant gas from the channel into the catalyst layer and improve performance. Here, we investigate experimentally the effect of in-line and staggered blockage configurations within a parallel flowfield and compare their fuel cell performance results with those of a baseline parallel flowfield without blockages. In the in-line configuration, three blockages are placed in each parallel channel such that they line up with each other when viewed laterally across channels. The staggered configuration also employs three blockages in each channel, but the blockages in adjacent channels are spaced apart such that the blockages in alternate channels line up when viewed laterally. Results show that the staggered configuration enhances cell performance by up to 28% over the baseline case, and by 18% when compared to the in-line case. Performance is improved even after accounting for the higher pumping power required to overcome the increased pressure drop due to the blockages. The presence of under-rib convection in the staggered configuration reduces the pressure drop by 18% when compared to the in-line case which only experiences under-block convection . Highlights: Experimental investigation of employing blockages in the channel of parallel flowfields of PEM fuel cells. Two configurations of blockages: in-line and staggered are studied and compared with the baseline case without blockages. The presence of blockages improves performance, with the staggered configuration being better than in-line and baseline cases. Improved performance is attributed to under-block and under-rib convection due to the blockages.